2013
DOI: 10.1111/j.1365-4632.2012.05595.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of Malassezia species isolated from Israeli patients with pityriasis versicolor

Abstract: Based on the PCR test, we have shown that M. globosa is probably most frequently associated with PV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…M . furfur has been shown to be rare or even absent, and when detected, is found in low proportions by molecular-based studies [ 3 , 12 , 47 50 ]. In contrast, it is often isolated by culture-based methods [ 51 53 ], which favor faster-growing organisms like M .…”
Section: Discussionmentioning
confidence: 99%
“…M . furfur has been shown to be rare or even absent, and when detected, is found in low proportions by molecular-based studies [ 3 , 12 , 47 50 ]. In contrast, it is often isolated by culture-based methods [ 51 53 ], which favor faster-growing organisms like M .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies found that M. pachydermatis may be transmitted to humans from pets [7,10]. M. pachydermmatis is the only lipid independent species while others are lipid dependent [11].…”
Section: Introductionmentioning
confidence: 99%
“…Malassezia species on both healthy (Findley et al, 2013) and diseased skin, such as pityriasis versicolor and seborrheic dermatitis ( Prohic & Ozegovic, 2007;Prohic, 2010;Amado et al, 2013;Lyakhovitsky et al, 2013;Lian et al, 2014;Rodoplu et al, 2014). M. sympodialis is the most frequent coloniser of healthy skin (Findley et al, 2013), but is found less frequently in Malassezia related-diseases, such as seborrheic dermatitis and pityriasis versicolour (Prohic & Ozegovic, 2007;Prohic, 2010;Amado et al, 2013).…”
Section: Globosa M Furfur M Restricta and M Sympodialis Are Tmentioning
confidence: 99%